Hotel Green Implementation for Future - A.A.Akeel; Jayawardhana S.A; M.A.P.M Perera; S.W.L.P de Silva; D.I De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
The online hotel management system was designed for the client hotel green, colombo, sri lanka. Currently, the client uses a manual system for management purposes where employees handle large amounts of data manually. The proposed system allows users to store and manipulated all the data in their database making their data handling process very effective. The proposed system is developed to cover the process of the hotel such as employee management, resource management, food management, rooms management, and user account management. The admin adds and updates the available rooms and foods, and customers can check the available rooms and order foods through the system. Admin adds, updates, and deletes employee details. Admin can mark the attendance of the employees. Admin can search relevant details. Admin can view details of all customers. The customers register and log in to the system. Customers can update and delete their accounts. A web application was developed to ensure that the customers of the hotel can make orders and reservations online. The system reduces data manipulation errors in the current process, resulting in considerable development in human resource utilization. It improves the client's relationship with their customers gaining profit for the business. The system is user-friendly, reliable, and efficient and its statistics all the customer requirements.